A critical theory enquiry in the development of number sense in Namibian first year pre-service secondary mathematics teachers - Naukushu, Shiwana Teeleni (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016